An Analysis of Buddhist Principles to Promote the Livelihood of Single Mothers in Thipphasot Community - et. al., Phrapalad Apisit Dhammavuddho (Seepalaew), (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The purposes of this research were 1) to study the livelihood of single mothers in Buddhist scriptures, 2) to analyse the Buddhist principles to promote the livelihood of single mothers in Thipphasot community. This research was qualitative research. The data were collected from documents, field work, in-depth interview, and to have empirical data, the descriptive analysis was used for data analysis. The livelihood of single mothers in Buddhist scriptures: after prince Siddhatha ordained monk in Buddhism, his wife (princess Bimba Devi) spent her life alone to look after her son. However, she could adjust herself to join the society. Her duty was to take care her son (Rahul Kumar). She accepted what happened. It could be reduced anxiety, indignation, and could adjust to the social environment. She was ready to face things, and accepted reality. The most importance of her duty was to take care her son completely. Analysis the Buddhist principles to promote the livelihood of single mothers in Thipphasot community: it maintained a family and took care their children in the society normally and happily. The principle of parents’ duty was used which consisted of reasoned attention (Yonisomanasikara), bases of sympathy (Sangahavatthu) which could be adopted in real life. Single mothers in Thipphasot community faced many problems until they could get through those obstacles, raised up the life to the development of life nicely, fed their children to the achievement. When they got through problems, they could become valuable single mothers. It was a model for learning for those who decided to pursue the life of a single mother in accordance with Buddhism.